Analisis Re-Branding Logo Halal Indonesia dalam Perspektif Teori Gestalt: Penelitian - Maysya Tri Putri; Daniel Handoko (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Ministry of Religion of the Republic of Indonesia through its official website and Instagram account in March 2022 established and released the "Indonesian Halal Label" logo. The release of the Indonesian Halal Label logo by the Ministry of Religion received various responses and views and even sparked debate and mutual opinions from various groups. Against the background of various polemics and controversies over the new design of the Indonesian Halal Label logo, this study will try to reveal the meaning of the Indonesian Halal Logo from the perspective of Gestalt theory. This study aims to explain the meanings of the Indonesian Halal Logo and to find out the elements of gestalt theory contained in the Indonesian halal logo. In this study, the researcher used a descriptive qualitative approach to data collection techniques, namely observation of the shape, color and typography/writing on the Indonesian halal logo. The results of the study show that the re-branding of the Indonesian Halal logo brought about significant changes in public perception of halal products. These changes occurred due to the application of the principles of Gestalt theory which emphasize similarity, unity, balance, experience and simplicity in the design of the new logo. This research makes an important contribution to the field of visual communication and branding, especially in the context of culture and religion in Indonesia.